2016
DOI: 10.1021/acsnano.6b03979
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Anode Material Sr2FeMo0.65Ni0.35O6−δ with In Situ Exsolved Nanoparticle Catalyst

Abstract: A metallic nanoparticle-decorated ceramic anode was prepared by in situ reduction of the perovskite Sr2FeMo0.65Ni0.35O6-δ (SFMNi) in H2 at 850 °C. The reduction converts the pure perovksite phase into mixed phases containing the Ruddlesden-Popper structure Sr3FeMoO7-δ, perovskite Sr(FeMo)O3-δ, and the FeNi3 bimetallic alloy nanoparticle catalyst. The electrochemical performance of the SFMNi ceramic anode is greatly enhanced by the in situ exsolved Fe-Ni alloy nanoparticle catalysts that are homogeneously distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
225
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(238 citation statements)
references
References 69 publications
13
225
0
Order By: Relevance
“…Especially, the exsolved Co and Ni nanoparticles on the surface of the layered perovskite show excellent cell performance (1.15 and 1.12 W cm −2 at 800 °C in H 2 , respectively) among developed ceramic anodes without adding any catalysts externally (Fig. 4d and Supplementary Table 3)28293031323334.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Especially, the exsolved Co and Ni nanoparticles on the surface of the layered perovskite show excellent cell performance (1.15 and 1.12 W cm −2 at 800 °C in H 2 , respectively) among developed ceramic anodes without adding any catalysts externally (Fig. 4d and Supplementary Table 3)28293031323334.…”
Section: Resultsmentioning
confidence: 95%
“…( b ) I – V curve and the corresponding power densities of the PrBaMn 1.7 Co 0.3 O 5+ δ (L-PBMCO) and PrBaMn 1.7 Ni 0.3 O 5+ δ (L-PBMNO) electrode using C 3 H 8 as fuel and ambient air as the oxidant at 800 °C. ( c ) Electrochemical performances of L-PBMNO anode in C 3 H 8 at 700 °C under a constant voltage of 0.6 V. ( d ) Comparison of the maximum power density at 800 °C in H 2 of the present work and other studies in the literature28293031323334.…”
Section: Figurementioning
confidence: 83%
“…However, this strategy usually produces a limited number of Ni‐based nanoparticles. Very recently, Du et al reported the fabrication of an Sr 3 FeMoO 7− δ and SrFe x Mo 1− x O 3− δ composites decorated with FeNi 3 alloy nanoparticles by reducing the Sr 2 FeMo 0.65 Ni 0.35 O 6− δ double perovskite oxide at a high temperature, showing favorable activity and high coking resistance 20. The number of Ni–Fe alloy nanoparticles deposited on the composite was high due to the conversion‐type reaction used to prepare it.…”
mentioning
confidence: 99%
“…The newly formed nanocomposite showed very high and stable activity for hydrocarbon and hydrogen electro‐oxidation reactions and favorable sulfur/coking tolerance. Recently, by controlling the reducing condition, Sr 2 FeMo 0.65 Ni 0.35 O 6− δ (SFMNi) double perovskite was converted into mixed phases containing Sr 3 FeMoO 7− δ , Sr(FeMo)O 3− δ , and FeNi 3 alloy nanoparticles . The electrochemical performance of the SFMNi anode was markedly improved by the in situ exsolved FeNi 3 alloy nanoparticles that were homogeneously distributed on the surface of the perovskite backbone.…”
Section: Nanostructured Perovskites For Electrocatalysis‐based Energymentioning
confidence: 99%